BIOLOGICAL EFFECT OF THE ELECTROMAGNETIC FIELD: BIOLOGICAL EFFECT OF THE ELECTROMAGNETIC FIELD - Vasilev , Dragomir (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
In this paper presents biological effect of the Electromagnetic field. The human body consists of cells, tissues, organs with different electrical characteristics. When an electric current flows through the human body, cells and tissues prevent the movement of charged particles. The value of the resistance depends on the type and condition of the cells, the value and frequency of the applied voltage and the duration.